Medieval Islamic political thought - Crone, Patricia, 1945-2015 (New Edinburgh Islamic surveys., 2004)
WINNER OF THE BRITISH-KUWAIT FRIENDSHIP SOCIETY PRIZE This book presents general readers and specialists alike with a broad survey of Islamic political thought in the six centuries from the rise of Islam to the Mongol invasions. Based on a wide variety of sources, it seeks to bring out the enormous scope and high level of historical (and, in some cases, contemporary) interest of medieval Muslim thinking on this subject. The author aims to make Islamic political thought easier for modern readers to understand by relating it to the contexts in which it was formulated, analysing it in terms familiar to the reader, and, where possible, comparing it with medieval European and modern thought. Guiding the reader through this complex history on a tour of one of the great civilizations of the pre-modern world, the book brings out the fascinating nature of medieval Islamic political thought, both in its own right and as the background to political thinking in the Muslim world today. Key Features Written by one of the most renowned scholars in the field All concepts have been glossed and all persons, events and historical developments have been identified or summarised, both on first encounter and in the index (where the number of the page containing the gloss will be emboldened) Specialists are addressed in the footnotes; non-specialists are free to skip these and read an uncluttered text